Examining the relationship between perceived teacher support and students’ academic engagement in foreign language learning: Enjoyment and boredom as mediators - Zhao, Yanlin; Yang, Lianrui (Frontiers in Psychology, 2022)
Teacher support, as an important contextual factor, has been a hot topic in educational research. Previous studies indicated that it is closely related to students’ academic engagement, learning motivation, emotional experiences, etc. However, this important contextual factor has been largely overlooked in the foreign language learning context. Given the important role of teacher support in students’ academic performance, the present study intended to investigate the relationship between perceived teacher support, enjoyment, boredom, and academic engagement. Data were collected from 1094 English as a foreign language (EFL) high school students in China. The results showed that students had moderate levels of perceived teacher support, enjoyment, and academic engagement, and a low level of boredom. Further correlation analyses indicated medium to large correlations between perceived teacher support, enjoyment, boredom, and academic engagement. Additionally, enjoyment and boredom collectively mediated the relationship between perceived teacher support and academic engagement. Implications of the present study and directions for future research are presented at the end.